Flexural Performance of Concrete Beams Reinforced with Epoxy Resin/Glass and Carbon Fibers Composites - Braga,Tiago Teixeira da Silva (2021)
Abstract Factors such as project and execution errors, lack of maintenance and inspection, and increases in loading can cause deficiencies to reinforced concrete structures. In this regard, there is the necessity of the application of structural reinforcement systems. This manuscript aims at the structural capacity analyses involving the bending of steel-reinforced concrete beams with additional reinforcement of polymer composites using glass and carbon fibers, and its comparison with regular reinforced concrete beams. Steel-reinforced concrete, polymeric composite, and hybrid beams (steel-reinforced concrete and polymeric composite combined) were submitted to the four-points bending test. Experimental and calculated results for the dimensioning of the beams were compared, allowing the validation of the calculation method and its implementation. It was possible to notice both the efficiency of the composite material applied as reinforcement, as well as the efficiency of the calculation models applied in this work.